Intellectual Capital dan Knowledge Management dalam Inovasi dan Kreasi Media Pembelajaran Berbasis Kemampuan 4C dan Literasi - Sylvia Ridwan (Proceedings of The ICECRS, 2019)
Education is the key to improving the quality of the nation's generation that is dynamic, following the needs and developments that exist. Industrial Revolution 4.0, where technological sophistication can do things that were previously considered difficult to do, also have an impact on education. This is a challenge for schools, especially in terms of preparing their educators to be able to form learners to be tough and ready to compete in the world of technology. Learning media is one of the factors that play an important role in learning that intersects with technology and gives a big influence on students. The use of internet-based technology has also been widely applied in learning media in schools. But the problem is, educators need to take an important role in terms of innovation and the creation of learning media that they use daily in classroom learning activities so as to support the needs of students in accordance with 4C skills (communicative, cooperative, creative, and critical thinking) and literacy culture. In this case, it is very important for schools to identify intellectual capital, namely the knowledge capital that is in school, which is the educators and how to properly manage all existing knowledge. This article examines the importance of intellectual capital and knowledge management in a school organization so that schools can manage existing knowledge in order to create innovation and learning media creation.